STRATEGI PENGEMBANGAN USAHA BORDIR KOMPUTER PADA CV GRAPIKA PROJECT PERKASA CIBINONG KABUPATEN BOGOR - Muhlis Muhlis; Dasmansyah Adyas; Zeze Zakaria Hamzah; Muhtadi Nugroho (Institut Teknologi dan Bisnis Dewantara, 2022)
The purpose of this study is to determine the strategy that becomes a priority in the business development of CV Grapika Project Perkasa Cibinong. The method that the author uses is a qualitative research method. This research was conducted at CV Graphika Project Perkasa Cibinong. This research was conducted at CV Graphika Project Perkasa Cibinong. The time of the research was carried out for 6 months, namely November 2020 - April 2021. Data analysis was carried out by SWOT analysis. Based on the results of the IFE matrix calculation for CV Graphika Project Perkasa for the overall internal factor weight score, a total score of 2.80 is obtained, which means that the value is at a strong level. Meanwhile, based on the results of the calculation of the EFE matrix for Radio Teman for the overall internal factor weight score, a total score of 1.90 is obtained, which means that the value is at a weak level. Based on the IFE matrix and the EFE matrix table, it is known that the IFE matrix value is 2.80 and the EFE matrix value is 2.81. The strategy that should be used by companies located in Cells II and IV is a market development strategy, so based on the results of the IFE and EFE matrices, the right strategy for CV Grapika Project Perkasa is a market development strategy.